Brazilian Psychiatric Association consensus on the ideal infrastructure and team for psychiatric emergency services - Leonardo Baldaçara; Flávia Ismael; Daniel Kawakami; Gislene Alves da Rocha; Elie Leal de Barros Calfat; Deisy Mendes Porto; Beatriz Ferroli Cavalcante; Beatriz Plotegher Zaramella; Flávio Veloso Ribeiro; Roberto Mendes dos Santos; Roberta Rossi Grudtner; Teng Chei Tung; et al. (Brazilian Journal of Psychiatry)
An integral part of Brazil’s public health system, psychiatric emergency services have been instrumental in improving qualified support for crisis situations involving mental disorders in an equitable, universally accessible, and humanized way. The purpose of this article is to present a systematic review and consensus on the infrastructure and the ideal team for psychiatric emergencies services in Brazil. The authors searched electronic databases including MEDLINE (PubMed), SciELO, and Cochrane, in addition to documents from the World Health Organization, the Brazilian Ministry of Health, and other authorities. Of the 6839 manuscripts found, 46 were included. The content analysis summarized consensus statements through the Delphi method, and, after a series of interactive versions, a final report was produced. Models for changing psychiatric emergency services are assessed. It was determined that the emergency care network must be supervised by qualified management, and all health equipment and units must be effectively integrated. Psychiatric emergency services need adequate infrastructure, qualified staff (including a psychiatrist), sufficient consultation and observation space, tools and resources for differential diagnosis, training for all staff members, and communication with the health care network to facilitate referrals following patient discharge. Standardized models should be available to public health managers to guide the development of new services and adjust existing ones, always seeking improvement. The authors propose a model of psychiatric emergency services.